Engineering phthalocyanines and carbon composites for use in sensing, microfluidics and dye sensitized solar cells - Klunder, Kevin Jay, author; Henry, Charles, advisor; Prieto, Amy, committee member; Reynolds, Melissa, committee member; Barisas, George, committee member; Jathar, Shantanu, committee member (Colorado State University. Libraries, 2018)
The focus of this thesis is on fundamental and applied electrochemistry in the areas of photovoltaics, sensors, and microfluidics. Photovoltaics are important as they are needed to reduce the amount of greenhouse gases, pollution, and reliance on finite energy sources that are currently associated with energy production. A thin film photovoltaic device known as a dye sensitized solar cell (DSSC) is studied in his work. Specifically the cathode of the DSSC is studied in detail. A new method to create a highly transparent and catalytic DSSC cathode coating is proposed. The phthalocyanine based coatings have ~97% transmittance at 550 nm and low charge transfer resistance of ~1.3 Ω cm2, representing one of the best cathode coatings in terms of transparency and charge transfer resistance to date. Electrochemical sensors and electrochemical microfluidics can be used to monitor air, water and soil pollution, both of which can occur from anthropogenic and/or natural sources. Quantifying this pollution is vital for human and animal safety. Electrochemical sensors are also used for health diagnostics and are commonly applied in blood glucose monitoring. It is projected that wearable forms of electrochemical sensors will emerge as a vital class of real-time point-of-care sensors to monitor health indicators in the near future. To advance the field of electrochemical sensors and electrochemical microfluidics low cost, easily miniaturized, patterned, and shaped electrodes are needed. The work here introduces a new fabrication method for carbon composites which enables electrodes to be patterned and made into micron features in a facile manor through solvent or melt processing. The composites are also shown to be easily integrated into microfluidic devices, demonstrated with the assembly of electrochemical droplet microfluidics. The ease of fabrication of the new composites represents a milestone for the widespread use of low cost carbon composites in complex electrochemical systems. Within this thesis, Raman, SEM, XRF, and a wide range of electrochemical redox species and techniques are used to determine what factors affect the electrochemical activity, capacitance, and conductivity of the carbon composites. Finally, phthalocyanines for uses in electrochemical catalysis are a recurring theme throughout the thesis. Chapter 4 is dedicated to creating new types of electropolymerizable phthalocyanines. Cobalt phthalocyanine is integrated into the carbon composites from Chapter 2 for uses in thiol oxidation and the sensing of thiols. The thiol of interest was dithiothreitol (DTT) which is used in the "DTT assay". The DTT assay is a chemical measure of oxidative potential of particulate matter, and is commonly used to try and understand health effects relating to air pollution. Here, low volume disposable cells, as well as flow based sensors are developed for the detection of DTT.
Keywords: DSSC; phthalocyanine; graphite; carbon composite